PENERAPAN LITERASI DAN NUMERASI DI SD KATOLIK LONDA LIMA MELALUI PROGRAM PEMBUATAN POHON ILMU DAN BERMAIN CONGKLAK - Matulessy, Yoin Meissy; Mbati, Miranti Dai; Awang, Richarlians Landu; Dilak, Eduard Dolon; Enda, Riwa Rambu Hada; ina, Anita Tamu (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The Community Service Learning (KKN-T) program conducted by students of Universitas Kristen Wira Wacana Sumba at SD Katolik Londa Lima aims to improve students' literacy and numeracy through creative activities, namely the creation of a knowledge tree and playing congklak. This program aims to address the low literacy and numeracy skills of 4th and 5th-grade students using observation and interview methods. The program involved students in creating a knowledge tree with an environmental theme for 4th grade and a counting theme for 5th grade, as well as the traditional game of congklak to strengthen arithmetic skills. Evaluation results showed an increase in students' interest and ability in literacy and numeracy after the activities were conducted. The activities also created a fun learning atmosphere, improved cognitive skills, and developed students' social skills. The creation of the knowledge tree helped visualize the lesson concepts, while playing congklak trained arithmetic and logical thinking abilities. This program has proven effective in supporting the development of basic competencies in students and promoting the values of literacy and numeracy in daily life. However, there were limitations in terms of time and supporting facilities. In the future, this activity is expected to be implemented sustainably and involve parents in supporting learning at home.